Предмет: Математика, автор: Аноним

помогите пожалуйста! это срочно ​

Приложения:

Ответы

Автор ответа: jekadva
1

Ответ:

3,8

Пошаговое объяснение:

= -9,2x + 16 - 3 + 2,6x + 1,8x - 12 = -4,8x + 1

при х = -7/12

-4,8x + 1 = -4,8*(-7/12) + 1 = 2,8 + 1 = 3,8

Автор ответа: sunflower364
1

Пошаговое объяснение:

-9,2х+16-3+2,6х+1,8х-12=-4,8х+1

 - 4.8 \times  ( -  \frac{7 }{12} ) + 1 =  -  \frac{24}{5}  \times ( -  \frac{7}{12} ) + 1 =  \frac{14}{5}  + 1 = 2 \frac{4}{5}  + 1 = 3 \frac{4}{5}

Похожие вопросы